A study of bovine and human carbonic anhydrases as a model enzyme system for CO2 hydration in post combustion capture. (June 2015) - Phan, Duong T.; Burns, Robert C.; Puxty, Graeme; Williams, Michelle; Haritos, Victoria S.; Maeder, Marcel
Graphical abstract: Highlights: Catalytic efficiencies of carbonic anhydrases on CO2 hydration were determined. Wild type bovine and human CAIIs were found to be the most efficient catalysts. Mutant bCAM9 is the least effective catalyst. Others have similar efficiencies. An analytical method to investigate enzymatic systems has been developed. Abstract: The Post Combustion Capture (PCC) process is currently the most applicable and effective approach to reduce emissions of CO2 from fossil fuel electricity generation. If the rate of CO2 hydration can be accelerated, the size of the absorber column can be reduced accordingly. Carbonic anhydrase type II (CAII), being one of the most active enzymes known for the reaction of CO2 with H2 O, is a promising catalyst for CO2 absorption in aqueous solution for PCC application. In this study, the catalytic efficiencies of human (hCAII), wild type bovine (wtbCAII), and a series of wtbCAIIs (bCAM1–bCAM9) structurally modified in an attempt to improve thermal and salt stability were determined by stopped-flow spectrophotometry at 25 °C. wtbCAII and hCAII were found to have the highest activity for the hydration of CO2 while bCAM9 was the least efficient catalyst (catalytic rate constants of 1.198(6) × 10 8, 1.14(1) × 10 8 and 0.77(2) × 10 8  M −1 s −1, respectively). The remaining mutants have similar catalytic efficiencies for CO2 hydration and fall in the range of 8.63(6) × 10 7 –1.072(2) × 10 8  M −1 s −1 . In addition to these results, this study also verifies the analytical method developed for the study of enzymatic systems.